Gamma-globulin Inhibits Superantigen-induced Lymphocyte Proliferation and Cytokine Production - Kumiko Kato; Tatsuo Sakamoto; Komei Ito (Allergology International, 2007)
Background: High-dose pooled human immunoglobulin (PHIG) treatment is sometimes effective in superantigen related inflammatory diseases, such as toxic shock syndrome and Kawasaki disease. Neutralizing antibody to superantigen might provide protection, but antigen independent immune regulation of PHIG is also a proposed mechanism. Methods: Staphylococcal enterotoxin B (SEB)-specific IgG antibody in PHIG products (Venoglobulin IH®) was detected by ELISA. The suppressive effect of PHIG or its fragments on proliferation and cytokine (IL-4 and IFN-γ) production from SEB-stimulated peripheral blood mononuclear cells was examined. Results: SEB-specific IgG was detected in PHIG products. PHIG (6.25-25 mg/ml) suppressed SEB-induced proliferation and cytokine production in a dose-dependent manner. Fab and F (ab’) 2 fractions of PHIG also suppressed the responses, but depletion of SEB-specific antibody from PHIG did not affect the inhibitory effects. The Fc fragment of PHIG also showed partial, but significant suppression. Conclusions: These data suggested the possibility that PHIG suppressed SEB-induced proliferation and cytokine production by some mechanisms independent of the presence of neutralizing antibody.